Analysis of Factors Affecting Housewife Using Tongol’s Bank Services in Plumbon Village According to the Islamic Perspective - Nayla Safarah; Hendri Hermawan Adinugraha; Sigun Ade Prayoga (Syamilah Publishing, 2024)
Needs continue to rise in both quantity and price, resulting in a gap between income and expenditure, even when people's incomes tend to remain even lower. In this case, people usually seek loans from someone or an institution that provides loans, both formal and informal. An informal bank, like a tongols bank, is preferred by the public. The aim of this research is to find out the factors that influence housewife borrowing in the bank and how the Islamic perspective affects debt borrowers. The method used in this research uses a qualitative method with a case study approach. The results of the research show that the Islamic view of debt practices is acceptable and encouraged by Islam. It can be done in practice and implementation in accordance with the rules, procedures, and rules of play applied in Islam. The factors leading to the occurrence of debt transactions in Plumbon's capital are the presence of urgent needs and lifestyle factors that are beyond capacity. Besides, the borrowing process is easy and can be done at any time. Their level of understanding of fiqih muamalah is so minimal that the people in Plumbon Hamlet are engaged in debt transactions that are clearly prohibited in Islam, that is, they owe to a tongols bank that clearly takes the profits that were required in the beginning. Besides, not all the terms and conditions of the debt of the borrower are also implemented by the customer.